Hodgkin Lymphoma - A Rare Neoplasm with Diagnostic and Therapeutic Challenges - Leite, Ana Bento; Rodrigues, Ana Raquel; Maia, Mariana; Novo, Filipa (Brazilian Journal of Case Reports, 2025)
The Classical Hodgkin Lymphoma (CHL) had four subgroups: nodular sclerosis, mixed cellularity, lymphocyte-rich and lymphocyte-depleted. Clinical diagnosis can be difficult because the symptoms are like other diseases. Lymphadenopathies and B symptoms may allow a diagnosis of suspicion, which must be confirmed by lymph node biopsy. One of its key features is the presence of mononucleated and multinucleated cells, the Hodgkin and Reed Sternberg cells. Chemotherapy (QT) ABVD (adriamycin, bleomycin, vinblastine, dacarbazine) is considered the standard therapy. The follow-up is very important due to the relapse risk and the potential late toxicity. The authors report a rare case of cHL nodular sclerosis IV-A, International Prognostic Score (IPS) 5 diagnosed by excisional biopsy of adenomegaly of the left armpit. The 18F-fluorodeoxyglucose positron emission tomography (18F-FDG PET) revealed a good response after QT. A rare bleomycin pulmonary toxicity was diagnosed, and he died. This paper aims to review the current knowledge concerning CHL.